Reticulocyte parameters as potential discriminators of recombinant human erythropoietin abuse in elite athletes - Parisotto, R.; Gore, C. J.; Hahn, A. G.; Ashenden, M. J.; Olds, T. S.; Martin, D. T.; Pyne, D. B.; Gawthorn, K.; Brugnara, C. (International Journal of Sports Medicine, 2000)
This study investigated using reticulocyte (retic) parameters as indirect markers of human recombinant erythropoietin (r-HuEPO) abuse in elite athletes. Absolute reticulocyte count (# retic), the per cell haemoglobin content of reticulocytes (CHr), reticulocyte haemoglobin mass per litre of blood (RetHb) and red blood cell:reticulocyte haemoglobin (RBCHb:RetHb) ratio were assessed using flow cytometry. Venous blood was drawn from 155 elite athletes from six sports during regular training to establish reference ranges (95% confidence interval) for these parameters. The reference ranges were compared with those of a non-athletic population (n = 23), four groups of athletes (n = 24) before and after exposure to simulated altitudes (2,500-3,000 m for 11-23 nights), two groups of elite cyclists (n = 13) before and after four weeks of training at natural altitude (1,780 and 2,690 m), and with those of non-athletic subjects from a separate study (n =24) before and 1-2 days after they were injected with 1,200 U x kg(-1) r-HuEPO over a 9-10 day period. Generally the changes induced by r-HuEPO injection exceeded by approximately 100% the magnitude of the changes associated with natural altitude exposure. Simulated altitude exposure did not significantly alter the reticulocyte parameters. From the sample of 155 non-users and 24 r-HuEPO users, the population mean and variance, as well as the 95% confidence limits for the population mean and population variance, were estimated. Relative to arbitrarily chosen cut-off levels, the confidence limits for the rate of true positives and rate of true negatives were also calculated. Based on the lowest rate of false positives and highest rate of true positives, the best discriminator between r-HuEPO users and non-users was # retic, marginally superior to RBCHb: RetHb ratio and RetHb. At a cut-off for # retic of 221 x 10(9)x L(-1) we could be 95% sure that we would find no more than 7 false positives in every 100,000 tests. We would expect to pick up 51.8% of users, and could be 95% sure of picking up at least 38% of current or recent users. This result highlights the potential power of retic parameters for detecting r-HuEPO abuse among athletes. However, the efficacy of these cut-offs for detecting r-HuEPO abuse is unknown if an athlete is a chronic user or stops using r-HuEPO several weeks before being tested. Int J Sports Med 2000 Oct;21(7):471-9